Pemberdayaan UMKM Melalui Transformasi Digital dan Pemasaran Berbasis Media Sosial: Pengabdian - M Alit Suryawan; Faiz Muqorrir Kaaffah; Bambang; Syahril; Ardi Hidayat (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The empowerment of MSMEs was implemented to encourage business actors to adapt to technological developments through digital transformation and social media-based marketing strategies. The implementation of the activities was carried out through the stages of preparation, implementation, mentoring and implementation, as well as evaluation and reporting. The results of the activity showed that the digital transformation training for MSMEs successfully improved participants' understanding and skills in utilizing technology and social media. During the two months of implementation, there was a significant increase in participant capabilities, with the level of understanding of digital transformation increasing from 45% to 82%. In addition, the number of MSMEs that maintain structured financial records increased from 26.6% to 90%, reflecting a shift from traditional management patterns to modern, technology-based management. In terms of marketing, MSMEs were able to develop more professional visual content, implement storytelling strategies, and utilize paid advertising. As a result, the social media engagement rate increased from 1.8% to 6.5%, accompanied by an average increase in sales of 35%.